Comparison of Adverse Reactions Caused by Olaparib for Different Indications - Zhou, Yujing; Zhao, Shengwen; Wu, Tong; Zhang, Han (Frontiers in Pharmacology, 2022)
Objective Meta-analysis of safety of Olaparib in the treatment of different indications. Methods The databases of PubMed, The Cochrane Library, EMbase, CNKI, WanFang Data and VIP were searched by computer to collect the research on the indications and the incidence of adverse reactions caused by Olaparib for different cancer types. The search time was from the establishment of the database to May 2022. After two researchers independently screened the literature, extracted the data and evaluated the bias risk included in the study, we used RevMan 5.4 software for meta-analysis. Results A total of 14 studies were included, with a total sample size of 5119 cases. By meta-analysis, the adverse reactions of Olaparib in the treatment of pancreatic cancer, breast cancer and ovarian cancer were compared. The results showed that fatigue (RR=1. 58, 95%CI [1.20-2.07], P=0.001) was the most serious in the treatment of pancreatic cancer with Olaparib. Anemia (RR=2.94, 95%CI [1.97-4.39], P < 0.00001), neutropenia (RR=1.37, 95%CI [0.80-2.33], P=0.25), nausea (RR=1.93, 95%CI [1.61-2.32], P < 0.00001) and vomiting (RR=1.96, 95%CI [1.59-2.41], P < 0.00001) were the most severe in ovarian cancer. Fatigue (RR=3.44, 95%CI [1.48-7.98], P=0.004) and vomiting (RR=1.09, 95%CI [0.42-2.81], P=0.86) were the most serious adverse reactions in the treatment of breast cancer with Olaparib. Anemia (RR=9.74, 95%CI [2.75-34.47], P=0.0004), neutropenia (RR=1.33, 95%CI [0.87-2.02], P=0.19) and nausea (RR=2.94, 95%CI [1.18-7.32], P=0.02) were the most severe in ovarian cancer. In addition, the incidence of decreased white blood cell count and hepatotoxicity in the treatment of breast cancer, and the incidence of decreased platelet count, constipation and abdominal pain in the treatment of ovarian cancer were higher than those in pancreatic cancer. Conclusion Current evidence showed that the risk of adverse reactions of Olaparib in the treatment of different indications is different, and specific analysis and treatment should be carried out for different cancer types. Due to the limitation of the quantity and quality of the included studies, the above conclusions need to be verified by more high-quality studies.